(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
يهدف هذا البحث إلى تحديد الشروط المثلى لفصل مركب التتراسيكلين وتحديده باستخدام عمودي الفصل الكرموتوغرافيينC8 و C18 والمقارنة بينهما بغية تطوير طريقة سريعة وحساسة، يُمكن اعتمادها في قياس هذا المركب باستخدام تقانة كروماتوغرافيا السائلة عالية الأداء وكاشف المصفوفة الديودية (High Performance Liquid Chromatography – Diode Array Detector HPLC-DAD). اعتمدت هذه الدراسة على تغيير أحد العوامل (نسب الطور المتحرك، درجة حرارة، سرعة تدفق الطور المتحرك، وطول موجة الامتصاص الأعظمي) وتثبيت العوامل الأخرى بغية الوصول إلى أفضل فصل مُمكن مترافقاً مع أفضل زمن احتفاظ ومساحة قمة للمركب المدروس. أظهرت الدراسة أفضلية عمود الفصل الكروماتوغرافي C8 مقابل عمود C18 لجهة مساحة القمة المفصولة 6.080 وزمن الاحتفاظ 4.169 ونقاوة الطيف 1000 للتركيز نفسه لمركب التتراسيكلين. تميز منحني المُعايَرة بخطية جيدة ومُعامل ارتباط R2= 0.99971 ممتاز ضمن مجال من التراكيز تراوح بين (1-100ppb). The aim of this research is to determine the optimal conditions for separation and determination of the Tetracycline compound using both chromatographic columns C8 & C18. The comparison between the above mention columns was made in order to develop a sensitive and rapid method which can be used to measuring this compound by High Performance Liquid Chromatography – Diode Array Detector HPLC-DAD. This study depends on changing one of the factors (Mobile phase ratio , Temperature, Flow- rate of the mobile phase, wavelength of the maximum absorption) and fixing the other factors in order to achieve the best possible separation conjugated with the best retention time (Rt) and the best peak area for the studied compound. The study showed that the area of the separated peak (6.080), the retention time (4.169) and the purity 1000 of the spectrum for the same concentration of Tetracycline were preferable by using chromatographic column C8. This result gives a preference for the chromatographic column C8 comparison to column C18. The calibration curve is found to have a good linearity and an excellent correlation coefficient R2= 0.99971 within a range of concentrations between(1-100ppb).